Perceived and functional health literacy and antibiotic use in children among Cypriot parents - Menikou, Joanna; Middleton, Nicos; Papastavrou, Evridiki; Nicolaou, Christiana (My University, 2023)
Background Several factors have been associated with antibiotic misuse leading to antibiotic resistance, an increasing public health problem. Health literacy (HL) may influence parents’ knowledge, attitudes, and practices (KAP) towards antibiotic use in their children. Methods A cross-sectional study was conducted with a convenience sample of parents of children, aged 6 months to 15 years, presenting in pediatric primary care centers across 3 Cypriot cities. Participants completed a KAP tool on antibiotic use. They also rated their HL competences using HLS-EU-Q47 and completed the NVS (Newest Vital Sign), a performance-based HL tool. Associations between parental KAP towards antibiotic use with both perceived health literacy (PHL) and functional health literacy (FHL) were explored. Results Among 203 parents (84.2% female, 84.3% tertiary education), preferred information source was associated with HL in different ways with higher FHL among those reporting using the internet for information regarding antibiotics in children (p = 0.04), whereas higher PHL was recorded among those reporting the doctor as information source (p = 0.01). An increase in the FHL score was associated with an increase in the knowledge (p = 0.01), attitudes (p = 0.01), and practices (p < 0.005) towards antibiotics. In contrast, no significant associations were observed between PHL and either knowledge or practices towards antibiotic use. However, antibiotic misuse, based on the number of recognized antibiotics from a list, was associated with lower PHL (p = <0.005). Parents with sub-optimal attitudes towards antibiotics had lower PHL scores on average (32.74, SD = 6.58 versus 36.30, SD = 7.77). Conclusions Better performance in a FHL measure among parents was with an increase in KAP towards antibiotic use in their children. Although this association did not appear consistent with PHL, a high number of parents with limited HL, either PHL or FHL, faced challenges in KAP towards antibiotic use in children. Key messages • Unnecessary use of antibiotics in children, problematic attitudes, and limited knowledge towards antibiotics among parents are associated with lower HL, either perceived or functional. • Assessing the association of parental KAP towards antibiotics and HL is important in gaining a comprehensive understanding of their HL and in developing targeted Public Health interventions.